Impact of Titanium Mining and Other Anthropogenic Activities on Malaria Positivity Rates and Parasitemia in Five Selected Study Sites in Msambweni Subcounty, Kwale County, Kenya - Edward Githinji; Collins Okoyo; Cassian Mwatele; Juma Mwatasa; Benard Chieng; Sylvie Araka; Henry Kanyi; Sammy Njenga; Judy Mwai (Journal of Parasitology Research)
Africa was home to 95% of malaria cases and deaths in 2021. The negative impacts of malaria can be aggravated by social–economic–environmental factors, more so agroeconomic practices such as irrigation, mining, and dam construction. The aim of this study was to investigate the impact of water harvesting, sugarcane farming, and mining activities on Plasmodium falciparum positivity rates and parasitemia densities in five selected sites in Msambweni Subcounty, Kwale Kenya. A cross-sectional concurrent mixed methods study was used to collect data. Kwale County was selected due to the high malaria endemicity possibly attributable to the suitable vector habitat characterized by the major anthropogenic activities. The study had five different arms of investigation; the first arm was the control (C), second dam (D) site, third sugarcane (S) site, fourth mining (M) site, and fifth dam–sugarcane–mining (DMS) site. Each of the 1025 consenting participants from 208 households provided a single blood sample for determining malaria prevalence and parasitemia using rapid diagnostic kit and microscopy. Overall, the malaria positivity rate was 22.9% by rapid diagnostic testing (RDT) and 20.1% by microscopy. P. falciparum observation by RDT was highest in the DMS site with 33.7% followed by S site with 26.8%, D site with 23.3%, and M site with 17.6%, and the least was the C site with 11.0%. The overall parasitemia density (parasite counts per 200 white blood cells) was 8.4 with a site-specific density of 18.7, 8.6, 7.1, 3.7, and 3.1 for DMS, S, D, M, and C sites, respectively. Univariable analysis of factors associated with malaria infection showed that participants in the DMS site were four times more likely to be infected with malaria (odds ratio OR=4.1, p<0.001) compared to those in the C site. Malaria vector and human host interactions are often enhanced by suitable environmental conditions especially ambient temperature which accelerate parasite growth in the mosquito and humidity. Anthropogenic activities may open up new breeding sites for the vector or increase human–Anopheles infective contact hours, hence the different positivity rates and intensities in P. falciparum transmission. The study results showed that prevalence of malaria and parasitemia was highest in areas where all the three anthropogenic activities were taking place. In the single-activity site, sugarcane farming predisposed participants to high malaria burden. Characterized relational interplay between these anthropogenic activities and P. falciparum parasitemia will be useful in developing tailored strategies towards optimized malaria control interventions in areas with and without anthropogenic activities.